Social Protection of Persons with Disabilities through Community Based Rehabiliation - An Analysis - Sr. Kochurani P.J and Lizy James (KILA Journal of Local Governance, 2013)
There exist a large disparity between rural and urban population in rehabilitat- ing and mainstreaming of People With Disabilities (PWDs). But we can overcome these obstacles through Community Based Rehabilitation and thereby we can ensure rights and social protection of the PWDs effectively. For the social protec- tion and reinstatement of the rights of per- sons with disabilities (PWDs), Nirmala Sadan, Muvattupuzha, has conducted a Community Based Rehabilitation (CBR) programme for PWDs in 44 wards of three gramma panchayaths of Ernakulum Dis- trict. The results of the study discussed in this paper reveal that, there is a re- markable improvement in the mainstreaming of PWDs especially in the areas of health, education, livelihood and rights and advocacy.